2014
DOI: 10.12691/ajfst-2-4-2
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of Some Physico-Chemical Properties of Soymilk-Based Juice with <i>Aframomum Danielli</i> Spice Powder

Abstract: The effect of Aframomum danielli powder on the shelf life of physico-chemical properties of soy-milk based juice was studied. In this paper, attempt was made to investigate the preservative effect of the powder of Aframomum danielli, a local spice, on the physico-chemical properties of blends of soymilk and juices from fruits and vegetable by prolonging its shelf life. This was done by adding 0.5-3.0grams of the spice powder to every 200ml of the blend, while the control samples had no spice. The juice quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 38 publications
2
7
0
1
Order By: Relevance
“…The results showed that the chemically treated and carbonated orange juice is as effective as pasteurized because it does not change the taste and it preserves more of its vitamins found in fresh-squeezed orange juice. Thus this result agrees previous studies (Murat, 2000;Polydera et al, 2003;Dauda and Adegoke, 2014). According to the Association of the Industry of Juices and Nectars from fruits and Vegetables of the European Union and the report by Kimball (1999), they stated that orange juice should contain at least 20 to 25 mg/100 ml of vitamin C (ascorbic acid) at the time of expiration of storage, which is about 50% of the initial amount.…”
Section: Vitamin C (Ascorbic Acid) Contentsupporting
confidence: 90%
See 4 more Smart Citations
“…The results showed that the chemically treated and carbonated orange juice is as effective as pasteurized because it does not change the taste and it preserves more of its vitamins found in fresh-squeezed orange juice. Thus this result agrees previous studies (Murat, 2000;Polydera et al, 2003;Dauda and Adegoke, 2014). According to the Association of the Industry of Juices and Nectars from fruits and Vegetables of the European Union and the report by Kimball (1999), they stated that orange juice should contain at least 20 to 25 mg/100 ml of vitamin C (ascorbic acid) at the time of expiration of storage, which is about 50% of the initial amount.…”
Section: Vitamin C (Ascorbic Acid) Contentsupporting
confidence: 90%
“…The differences obtained in flavour and aroma could be attributed to the different compounds formation based on the different methods of processing and storage of the tested samples of orange juices (Adubofuor et al, 2010). Moreover, orange juice can lose its flavour, colour or other quality factors due to non-enzymatic browning reactions during processing or storage of the juices (Dauda and Adegoke, 2014). The result of this study which showed off-flavour and aroma is also in support of the reports of Moshonas and Shaw (1998), they reported that orange juice can lose some of its fresh flavour during storage because of decreased levels of volatile flavour constituents, thus developing a stable flavour.…”
Section: Sensory Analysissupporting
confidence: 83%
See 3 more Smart Citations